A critical overview of the current myofascial pain literature – March 2016. Issue 2 (April 2016) - Dommerholt, Jan; Hooks, Todd; Finnegan, Michelle; Grieve, Rob
Summary: The worldwide interest in myofascial pain syndrome (MPS) and trigger points (TrPs) is reflected in the increasing number of publications. In this overview of the literature, we included 26 studies, case reports and review articles by authors from 18 different countries. Several research groups are exploring the characteristic of TrPs such as Chen and colleagues, who continued their work on the quantification of the taut bands. Meng and colleagues studied the relationships between TrPs and central sensitization, while Yu and colleagues examined the electrophysiological characteristics that occur as a result of active TrPs. Several researchers used objective measurements to determine clinical outcomes, such as Koppenhaver and colleagues who measured objective changes in the function and nociceptive sensitivity of lumbar multifidus muscle subjects with low back pain. Turo and colleagues quantified muscle tissue changes after dry needling in chronic myofascial pain using elastography. Multiple studies explored various treatment options for TrPs, such as dry needling, injections with lidocaine or granisetron, traditional Thai massage, self-myofascial release, kinesiotaping, and monochromatic infrared photo energy, among others.